(untitled) (Castilla. Estudios de Literatura, 2026)
For a long time, academic disdain for comparative literature, or comparativism, stemmed from the same reason why the canon of other literatures was disregarded within the fields of national literatures studies. This article proposes a critical review of comparative literature throughout its history and a subsequent theoretical exploration of what it means today, in the cultural context of globalization, to speak of comparative literature, general literature, or world literature. This is an era, as the article examines, in which comparative literature can perhaps only be understood as a problem, and world literature as one of its possible solutions.